Greening the Curricular of Building Construction Trade for Environmental Sustainability Through Fostering Waste Minimisation Skills - Hamza, Samaila; Musta'amal@Jamal, Aede Hatib; Kamin, Yusri (Journal of Technical Education and Training, 2020)
Waste minimisation skills became the subject of this research because construction industry generates lots of waste during and after construction. Therefore, the purpose of this quantitative study was to develop a conceptual model for integrating waste minimisation skills in Building Construction Trade (BCT) at technical colleges in Nigeria. This paper is aimed at exploring the negative effects of building construction wastes to environmental sustainability and identifying, using questionnaire through experts in building construction the important areas of waste minimisation skills suitable to be embedded into the curricular of building construction trade.  Analysis of the identified important areas via Descriptive statistics (mean and standard deviation), Exploratory Factor analysis (EFA) and Confirmatory factor analysis (CFA) were used to analyse the data which will immensely contribute to the body of knowledge. The findings for this study include ability to manage waste, including custom diversion plans tailored to the project opportunities; consider that the selection and use of recyclable materials and products to minimise waste; and recycle waste generated from the process of intentional dismantling all or portions of a building. Using the results of the analysis, the research formulates a waste minimisation skills integration model, while Structural Equation Modelling (SEM) was used to validate the modified model and viable suggestions were made to the government for the adoption and practical implementation of the model by fostering the identified areas of the waste minimisation skills elements into the curriculum of building construction trade at technical colleges in Nigeria with the aimed for the  environmental sustainability.